THE EFFORT OF ABCGM TO ESTABLISH BUSINESS CULTURE IN WEST JAVA UNIVERSITIES THROUGH BUSINESS INCUBATOR - Ida Hindarsah; Bulan Prabawani; Sulistia Suwondo (Lembaga Penelitian Universitas Pasundan, 2021)
Indonesia is a developing country in Asia, whose economic development still depends on foreign investment. MSME is an alternative business unit that can encourage domestic economic growth that can be released from the dependence of foreign investment. The low number of MSMEs compared to other countries in Asia and the vulnerability of MSMEs unable to compete in the market in the era of globalization. Make the government fund various stakeholders to be established and develop business incubators, including universities. With the adoption of this policy, universities in West Java began to create and build business incubators. This article is intended to describe the process of establishing and developing a university business incubator in West Java. The method used in this research is qualitative research with data collection techniques through data observation and literature study. The results of the study that discussed the establishment of a university business incubator in West Java were carried out in collaboration with lecturers with international non-profit organizations.